2018
DOI: 10.1002/jcp.26561
|View full text |Cite
|
Sign up to set email alerts
|

Quaking promotes the odontoblastic differentiation of human dental pulp stem cells

Abstract: Odontoblastic differentiation of human dental pulp stem cells (hDPSCs) is essential for the formation of reparative dentin after dental caries or injury. Our previous studies have demonstrated that krüppel-like factor 4 (KLF4) is a critical transcription factor that promotes the odontoblastic differentiation of hDPSCs. Analysis of the microRNA binding sites within the 3'-UTR of KLF4 revealed that QKI, an RNA-binding protein, shared the most microRNAs with KLF4, presumably served as a "competent endogenous RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…We also performed several in vitro experiments and verified that KLF4 is an important transcription factor that promotes the odontoblast differentiation of mouse dental pulp cells and mDPCs . Furthermore, in vitro experiments revealed that, during odontoblast differentiation, klf4 is posttranscriptionally regulated by mir‐143 and mir‐145, and Sp1 and Qki were also found to act as competent endogenous RNAs (ceRNAs) of KLF4 to promote odontoblast differentiation in vitro . However, the in vivo role of KLF4 in the commitment of dentin progenitors or dentinogenesis has not been extensively described.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…We also performed several in vitro experiments and verified that KLF4 is an important transcription factor that promotes the odontoblast differentiation of mouse dental pulp cells and mDPCs . Furthermore, in vitro experiments revealed that, during odontoblast differentiation, klf4 is posttranscriptionally regulated by mir‐143 and mir‐145, and Sp1 and Qki were also found to act as competent endogenous RNAs (ceRNAs) of KLF4 to promote odontoblast differentiation in vitro . However, the in vivo role of KLF4 in the commitment of dentin progenitors or dentinogenesis has not been extensively described.…”
Section: Introductionmentioning
confidence: 70%
“…(19,20) Furthermore, in vitro experiments revealed that, during odontoblast differentiation, klf4 is posttranscriptionally regulated by mir-143 and mir-145, (21,22) and Sp1 and Qki were also found to act as competent endogenous RNAs (ceRNAs) of KLF4 to promote odontoblast differentiation in vitro. (23,24) However, the in vivo role of KLF4 in the commitment of dentin progenitors or dentinogenesis has not been extensively described.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry assay was used to further characterize the hDPCs. The experiment were performed according to the protocol described before . Results showed that mesenchymal stem cell markers like CD44 (FITC, BioLegend, San Diego, CA) and CD90 (FITC, BioLegend) were dominantly positive in hDPCs population while CD34 (FITC, BioLegend) and CD45 (FITC, BioLegend), which are hematopoietic markers, showed negative signals (Supplemental Figure S1 B‐E).…”
Section: Methodsmentioning
confidence: 99%
“…Because real native odontoblasts display long cell processes embedded into the dentinal tubules, the isolation of real odontoblasts will lead to damage and cell death. Therefore, induction of dental papilla cells into odontoblastic cells in vitro has been widely used as an excellent model for odontoblast-related experiments in many reports ( Chen et al, 2015 ; Yang et al, 2015 ; Zhang et al, 2015 ; Iwamoto et al, 2017 ; Li Q. et al, 2018 ; Li s. et al, 2018 ; Zheng et al, 2020 ). In this study, we confirmed these cells as odontoblastic cells as described previously ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%